The Influence of Promotion and Corporate Image on Customers Decisions to Use Haji IB Maslahah Savings at Bank Jabar Banten Syariah - Sonjaya, Adang; Sule, Babayo (Fakultas Ekonomi dan Bisnis Islam, 2023)
The decision of customers to engage with Islamic banking products is influenced by factors that cater to their desires and needs, with Hajj being a profound aspiration for every Indonesian Muslim. This study aims to scrutinize the impact of promotion and corporate image on customer decisions regarding the utilization of the Haji iB Maslahah savings product at Bank Jabar Banten Syariah KCP Cikurubuk. Questionnaires were distributed to customers of Mudharabah savings products at the mentioned bank, yielding 20 purposively sampled respondents. The data analysis involved multiple linear regression. The findings indicate that both promotion and corporate image collectively influence customer decisions, supported by F counts > F tables (7.819 > 3.59). On a partial level, promotion significantly impacts customer decisions (t calculate > t table: 3.345 > 2.10092), while corporate image, unfortunately, does not have a significant effect on customer decisions (t calculate < t table: 0.683 < 2.10092). This underscores the critical importance of robust promotion strategies and the ongoing maintenance of a positive corporate image. The implications of this research extend to Islamic banking, urging continual enhancement of promotion efforts and corporate image management to enhance customer decisions in favor of their products.